Preparation and Preservation of Maize Stalk Fodder (Bangladesh Journal of Agricultural Research, 2023)
Shortage of feed supply of the cattle during the dry season or flood period is an important issue which could be partially met by maize stalk. An experiment was conducted to prepare maize stalk fodder for cattle. The BARI chopper was improved for chopping maize stalk (MS) in smaller size (7-8mm) by adding blades and make the chopper safe by adding casing. The capacity of the BARI chopper was 745 and 425 kg/h with fresh and dried maize stalk, respectively. Total chopping cost per hour was Taka 0.23 per kg. The chopped maize stalk in both fresh and dried conditions with different combinations were served to the cattle and found that smaller sized chopped piece of both dried and fresh maize stalk could be feed in both raw and mixing with salt, wheat bran and water with little molasses. Maize stalk block also prepared with different combinations and found that block made by liquid Gur was better in both physically and cattle likeness. Total cost of block per kg was Tk. 13.85, 31.35, 28.85 and 36.35 for MS block 1, MS block 2, MS block 3 and MS block 4, respectively. Chopped and dried maize stalk were preserved in polybag, open drum and store room were liked by the cattle up to three months of the storage. Flatten and dried maize stalk were not liked by the cattle due to their long size and hardness. Bangladesh J. Agril. Res. 47(3): 333-342, September 2022